Analytical Study of Some Kinematical Variables Affecting Turnover Phase in 200m Freestyle Swimming in Specialized Schools Swimmers - Thamer, Ahmed; Hamdan , Husham (Journal of Physical Education, 2022)
The research aimed at identifying some kinematical variables affecting turnover phase in 200m freestyle swimming in swimmers from specialized school. The subjects were (3) swimmers who were studied suing motor analyses with Kinovea motor analysis program to come up with kinematical variables for each swimmer. The variables were compared to conclude that there are significant differences in variable values of the swimmers themselves as well as differences among them after each 50m of the 200m. The results showed great variance in achievement total time a matter that require reform in artistic performance as well as developing some physical trains of specialized swimming schools swimmers in 200m freestyle to decrease total time thus improving achievement.